Guide :

# 5(2x-3)=-15+10x

I'm not sure what to put for in awser for this Solve the equation if possible. 5(2x-3)=-15+10x so then 10x-15=-15+10x subtract 10x from both sides then its -15=-15 Simplified to 1=1   there for X can be anything

## Research, Knowledge and Information :

### Distribute: 5(2x + 3) 10x + 15 ... - OpenStudy

Distribute: 5(2x + 3) 10x + 15 7x + 8 10x + 25 7x + 3Write it properly... After 10x + 15, what have you written??....

### 5(2x-3)=15 - Get Easy Solution

Simple and best practice solution for 5(2x-3)=15 equation. Check how easy it is, and learn it for the future. ... (-3 + 2x) = 15 (-3 * 5 + 2x * 5) = 15 (-15 + 10x) ...

### Solve 10x-5(2x+3)=15 Tiger Algebra Solver

Tiger Algebra - {10*x-5*(2*x+3)-(15)=0}Solve your HOMEWORK assignments with Tiger Algebra. Free, Shows Steps ... (10x - 5 • (2x + 3)) - 15 = 0 Step 2 ...

### 5(2x+3) A 10x+15 B 7x+8 C 10x+25 D 7x+3?

5(2x+3) A 10x+15 B 7x+8 C 10x+25 D 7x+3? Answer for question: Your name: Answers. Answer #1 | 20/10 2015 19:12 Option A ...

### factor completely -5x^2+10x-15? a. -5(x^2-2x+3) b. -1(x^2-10x ...

Factor −5x^2+10x−15 −5x^2+10x−15 =−5(x^2−2x+3) Answer = A) Comments; Report; 1 4 1. Thanks. 1. This question is archived. Ask new question. The Brain; Helper;

### 5(2x)-3=20x+15 - solution - Get Easy Solution

Simple and best practice solution for 5(2x)-3=20x+15 equation. Check how easy it is, ... 5 * 2x + -3 = 20x + 15 Multiply 5 * 2 10x + -3 = 20x + 15 Reorder the terms: ...

### Solve the following 5(2x-3)=15 - Brainly.com

Solve the following 5(2x-3)=15 - 1866856. 1. Log in Join now Katie; ... Simplifying 5(2x + -3) = 15 Reorder terms: 5(-3 + 2x) = 15 (-3 * 5 + 2x * 5) = 15 (-15 + 10x) ...

### 5(2x-3)=15 ? - OpenStudy

5(2x-3)=15 ?distribute 10x -15 = 15 x = 3. you have to be able to solve things like that, ... OpenStudy is now Brainly! ... 5(2x-3)=15 that means 5 times ...

## Suggested Questions And Answer :

### Help me to solve 2/3(5X-1)+1/4(4X-3)≤1/6(7Z+2)+31/4=

me assume thats spozed tu be (2/3)(5x-1) +(1/4)(4x-3) <= (1/6)(7z+2) +(3/4) or 8*(5x-1) +3(4x-3) <= 2(7z+2) +9 40x -8 +12x -9 <=14z+4+9 52x -17 <= 14z+13 52x <= 14z+ 13+17 52x <=14z+30 26x <=7z+15

### 3(7-9x)-5(5x+1)=-8(9x-4)

3(7 - 9x) - 5(5x + 1) = -8(9x - 4) distribute on both sides: 21 - 27x - 25x - 5 = -72x + 32 combine terms on the left: 16 - 52x = -72x + 32 add 52x to both sides: 16 = -20x + 32 subtract 32 from both sides: -16 = -20x divide both sides by -20: x = -16/-20 = 4/5

### 6.5(8x+6)-6(6.5x+3.5)

6.5*(8x+6) -6*(6.5x+3.5) =52x +39 -39x -21 =(52x -39x) +(39-21) =13x +18

### 2x + x + 3 = x + 2 - 5

2x + x + 3 = x + 2 - 5 2x + x + 3 = x + 2 - 5 2x + x + 3 = x + 2 - 5 3x + 3 = x - 3 3x + 3 - x = x - 3 - x 2x + 3 = -3 2x + 3 - 3 = -3 - 3 2x = -6 2x/2 = -6/2 x = -3

### 5 11 49 223 ? options 1) 789 2) 769 3) 753 4) 764 5) none of these

One solution gives 637 as the next term, which is none of the first 4 options in the answers, but satisfies the 5th. The formula (52x^3-108x^2+74x+15)/3 gives the terms with x=0, 1, 2, 3 and 637 for the next term (x=4). I suspect this isn't the solution you were looking for.

### How to solve 5/x - 2/3x = 17 1/3

5/X - 2/3X = 17 1/3 Yes, you're right; the best thing to do would be to turn 17 1/3 into the fraction 52/3. Then the easiest way to continue is probably to multiply both sides of the equation by X: 5 - (2/3) = (52/3)X Then put the left hand side of the equation over the same denominator: 5x(3/3) - (2/3) = (52/3)X (5x3)/3 - (2/3) = (52/3)X 15/3 - 2/3 = (52/3)X (15-2)/3 = (52/3)X 13/3 = (52/3)X Then multiply both sides of the equation by 3: 13 = 52X Then divide both sides by 52, So,   X = 13/52 This can then be simplified: So,   X = (13/13)/(52/13) X = 1/4

### 10x + 3 = 15

10x+3=15 10x=15-3 10x/10=12/10 X=12/10 X=6/5

### how do I solve 10x+3=15

10x+3=15 10x=15-3 10x=12 x=12/10 x=1.2(ans)

### solve by the substitution method y=x-1 2x+y=5

2x+(x-1)=5                                 y=x-1 2x+x-1=5                                   y=2-1 3x-1=5                                       y=1 3x=6 x=6/3 x=2